PENGEMBANGAN SISTEM DETEKSI KEBOCORAN PIPA AIR PADA RUMAH KOS BERBASIS WEB - Achmad Sulthon Hadi; sujono (LPPM Politeknik Pratama Kendal, 2026)
Water wastage in boarding houses is often caused by undetected pipe leakage due to the lack of real-time monitoring systems. This condition can lead to increased operational costs and potential structural damage. This study aims to develop a web-based water pipe leakage detection analysis system using Internet of Things (IoT) technology. The system utilizes an ESP8266 (microcontroller) and a water flow sensor to identify abnormal water flow patterns. Data is processed using PHP and MySQL and presented through a web-based dashboard in the form of graphs and tables. The system was developed using the Waterfall method. The results indicate that the system is able to accurately distinguish water flow characteristics. Based on blackbox testing, all functional features achieved 100% validity. The system successfully identifies a